2020
DOI: 10.1177/0020764020919787
|View full text |Cite
|
Sign up to set email alerts
|

Online media reporting of suicidal behaviour in Ghana: Analysis of adherence to the WHO guidelines

Abstract: Background: Irresponsible media reporting of suicide is a potential risk for copycat suicide. There is a paucity of studies from sub-Saharan Africa on the quality of media reporting of suicide. Objectives: We assessed the compliance of Ghanaian online media outlets with the World Health Organization (WHO) guidelines for media reporting of suicide. Methods: We searched 10 local media outlets with strong online presence in Ghana, to identify suicide-related news reports from 2000 through 2019. We applied summati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
(112 reference statements)
2
6
0
Order By: Relevance
“…A similar pattern of news presentation reported in the African countries like Ghana where most of the news reports failed to comply with the WHO guidelines (Quarshie et al, 2020). Nonetheless, a slightly different situation has been reported in Egypt where media complied with few of the guidelines, such as not defining suicide as ‘success’ or ‘failure, not using images or videos, not mentioning the suicide note of a victim and not adding a quote about the victim (Mesbah, 2014).…”
Section: Discussionsupporting
confidence: 66%
“…A similar pattern of news presentation reported in the African countries like Ghana where most of the news reports failed to comply with the WHO guidelines (Quarshie et al, 2020). Nonetheless, a slightly different situation has been reported in Egypt where media complied with few of the guidelines, such as not defining suicide as ‘success’ or ‘failure, not using images or videos, not mentioning the suicide note of a victim and not adding a quote about the victim (Mesbah, 2014).…”
Section: Discussionsupporting
confidence: 66%
“…Prior research has demonstrated that dissemination of media guidelines specifically can lead to improved reporting; however, effects can be variable and may fluctuate over time and, often, journalist awareness and use of guidelines can be low, particularly in low- and middle-income countries. 32 , 46 66 The discrepancy between our encouraging putatively harmful/protective element outcomes and our stark Gestalt narrative findings suggest that the current lists of “dos” and “don’ts” provided to journalists may not only miss the forest for the trees, but indeed leave suicide-related media reporting in the wrong forest altogether. It is worth underscoring that societal messaging and narratives about suicide and its prevention appear to differ from public messaging about almost any other health outcome.…”
Section: Discussionmentioning
confidence: 66%
“…Some studies have shown that the way suicide deaths are reported by the media has an impact on community suicide rates (Niederkrotenthaler, et al, 2010;Quarshie, Andoh-Arthur, Asante, & Asare-Doku, 2020;Stack, 2009;Pirkis, Burgess, Francis, Blood, & Jolley, 2006). Irresponsible suicide reporting, particularly when the suicide stories are publicized in graphic detail appears to trigger copycat behaviours (Niederkrotenthaler, et al, 2010;Wang & Xiangdong, 2012).…”
Section: Discussionmentioning
confidence: 99%